OPTIMALISASI KEMAMPUAN REPRESENTASI MATEMATIS SISWA MELALUI PROJECT-BASED LEARNING BERBANTUAN SOFTWARE GEOGEBRA - Zakiya Aulia Ilma; Turmudi Turmudi (Universitas Singaperbangsa Karawang, 2021)
This study has the following objectives: 1) measuring the increase in students' mathematical abilities who learn through Project-based Learning assisted by Geogebra software compared to students who learn through ordinary learning; 2) measuring the achievement of students' mathematical representation abilities who learn through Project-based Learning assisted by Geogebra software compared to students who learn through ordinary learning; 3) measuring the average achievement of students' mathematical representation abilities who learn through Project-based Learning assisted by Geogebra software compared to the Minimum Completeness Criteria (KKM) for mathematics of 75. This study is a quasi-experimental study with a non-equivalent control group design, which was conducted on students class XI at SMA Negeri 1 Telukjambe Timur with the subject Integral. The results of the study show that: 1) the increase in students' mathematical representation abilities who learn through Project-based Learning assisted by Geogebra software is better than students who learn through ordinary learning. 2) the achievement of mathematical representation abilities of students who learn through Project-based Learning assisted by Geogebra software is better than students who learn through ordinary learning. 3) the average achievement of students' mathematical representation abilities who learn through Project-based Learning assisted by Geogebra software reaches KKM 75. Keywords: Project-based Learning; Geogebra Software; Students' Mathematical Representation Ability.